Molecular screening and the clinical impacts of BCR-ABL KD mutations in patients with imatinib-resistant chronic myeloid leukemia - TUĞLULAR, AYŞE TÜLİN; ATAGÜNDÜZ, IŞIK; AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE; TOPTAŞ, TAYFUR (SPANDIDOS PUBL LTD, 2017)
The present study aimed to detect the frequency of kinase domain (KD) mutations in order to evaluate their clinical significance and functional importance in 45 patients with chronic myeloid leukemia (CML) who were resistant to imatinib therapy. Sanger sequencing was used (45 patients), along with allele-specific oligonucleotide polymerase chain reaction (ASO-PCR; 3 patients), for the screening of mutations. BCR/ABL KD was amplified by nested PCR and sequencing was performed. Secondly, ASO-PCR was performed to confirm the results of the sequence analysis for E255K mutations. Mutations were detected in 11/45 patients (24.44%) via Sanger sequencing. D241G (4.4%), C369C (4.4%), K285N (2.2%), A380T (2.2%) and A366V (2.2%) mutations were detected. E255K (8.8%) was detected by ASO-PCR and Sanger sequencing. Mutations are a primary reason for suboptimal responses, loss of response and resistance to imatinib. In particular, the E255K mutation, which is characterized by resistance to imatinib and nilotinib, was detected in four patients. Analyzing the mutations and monitoring patients with CML may improve their prognosis and survival rate. ASO-PCR assays will be beneficial for the routine monitoring of mutations.
Keywords: chronic myeloid leukaemia; breakpoint cluster region abelson kinase domain; mutation; imatinib resistance; DNA sequencing; KINASE DOMAIN MUTATIONS; DYNAMICS; MUTANTS; ALLELE